Social Impact of State Charity on Vulnerable Populations: An Ethnographic Study of the low income Families in Baltistan - Batool, Arifa; Mosvi, Syeda Sakina; Rana, Abdul Waheed (Journal of Development and Social Sciences, 2025)
This study explores the social impact of state charity programs and examines how such initiatives influence the well-being of vulnerable individuals. Baltistan’s people who are in hardships which are associated with geographic isolation, traditional practices, and environmental problems, how charity programs addressed by the state correspond with the locals’ and communities’ experience and expectations. Ethnographic approach to explore the lived experiences and direct financial and material support in addressing immediate needs, identify the disadvantages of these programs with a specific focus on the Benazir Income Support Program (BISP) in Baltistan. The finding of this study show BISP provide short-term relief, they are not sustainable for long-term development. It highlights the need to enhance individual capabilities and expand opportunities. Recommended as a strategy to break cycles of dependency and encourage long-term societal transformation. The study advocates for a more sustainable approach to state charity, ensuring lasting social progress and improved livelihoods for vulnerable populations.